Applying TADF Emitters in Bioimaging and Sensing—A Novel Approach Using Liposomes for Encapsulation and Cellular Uptake - Smith, Poppy O.; Black, Dominic J.; Pal, Robert; Avó, João; Dias, Fernando B.; Linthwaite, Victoria L.; Cann, Martin J.; Pålsson, Lars-Olof (Frontiers in Chemistry, 2021)
A new method for facilitating the delivery, uptake and intracellular localization of thermally activated delayed fluorescence (TADF) complexes was developed. First, confinement of TADF complexes in liposomes was demonstrated, which were subsequently used as the delivery vehicle for cellular uptake. Confocal fluorescence microscopy showed TADF complexes subsequently localize in the cytoplasm of HepG2 cells. The procedures developed in this work included the removal of molecular oxygen in the liposome preparation without disrupting the liposome structures. Time-resolved fluorescence microscopy (point scanning) showed initial prompt fluorescence followed by a weak, but detectable, delayed fluorescence component for liposomal TADF internalized in HepG2 cells. By demonstrating that it is possible to deliver un-functionalized and/or unshielded TADF complexes, a sensing function for TADFs, such as molecular oxygen, can be envisaged.